An Experimental Study of the Impact of Judgment-Based Marketing Models - McIntyre, Shelby H. (Management Science, 1982)
The impact of a decision calculus model on decision quality is assessed in a laboratory setting. An experimental design assesses the effects of: (a) the size of the problem (i.e., the number of control units over which allocations are to be made), (b) the noise-to-signal ratio in the market and (c) individual differences among the model users. The aspects of individual differences studied are: (1) time taken on the task, (2) mathematical ability and (3) cognitive style. The main experiment involved 96 subjects in a full factorial design. In general, the decision calculus model had a beneficial impact on a broad range of decision quality measures, particularly profit achievement.